Hubungan Mutu Pelayanan Terhadap Kepuasan Pasien: Studi Kasus Pasien Rawat Inap Rumah Sakit Umum Kabupaten Bombana 2021 - Salfia Salfia; Sartiah Yusran; Juminten Saimin (Jurnal Manajemen dan Administrasi Rumah Sakit Indonesia (MARSI), 2021)
This study analyzes Patient Satisfaction at the BLUD General Hospital Bombana Regency in terms of service quality model aspects (reliability, assurance, physical evidence, attention, and responsiveness. This research is a quantitative study with a cross-sectional study design—data collection techniques using a questionnaire. The results showed a significant relationship between reliability, assurance, tangibles, empathy, and responsiveness with patient satisfaction with a value (ρ value = 0.000 <0.05). From the study results, it was concluded that from the aspect of reliability, assurance, physical evidence, attention, and responsiveness of officers in providing services and education to patients at the BLUD of Bombana District General Hospital, it could affect the level of patient satisfaction. In this study, assurance and empathy become the dominant criteria for assessing patient satisfaction